A physics-based zero-dimensional model for the mass flow rate of a turbocharger compressor with uniform/distorted inlet condition. (August 2019) - Song, Kang; Zhao, Ben; Sun, Harold; Yi, Weilin
Turbocharger compressor, when fitted to a vehicle, usually operates with a curved inlet pipe which leads to distorted inlet flow field, hence deteriorating compressor flow capability. During the measurement of compressor performance, turbocharger-engine matching and controller design, the inlet flow field is, however, assumed to be uniform, which deviates from the real-world conditions. Consequently, the overall system performance could be compromised if the inlet distortion effect is ignored. To address this issue, in this article, a turbomachinery physics-based zero-dimensional model was proposed for the mass flow rate of a compressor with distorted inlet flow field due to 90° and 180° bent inlet pipe. The non-uniform flow is approximated as two-zone flow field, similar to parallel compressors, with the total pressure deviation between two zones modeled as a function of the flow velocity and pipe geometry. For each flow zone, the corresponding mass flow rate is estimated by approximating each sub-compressor as an adiabatic nozzle, where the fluid is driven by external work delivered by a compressor wheel governed by Euler's turbomachinery equation. By including turbomachinery physics and compressor geometry information into the modeling, the model achieves high fidelity in compressor map interpretation and extrapolation, which is validated in experiments and the three-dimensional computational fluid dynamic simulation.